Importance of the CNGA4 channel gene for odor discrimination and adaptation in behaving mice - Kelliher, Kevin R. (The National Academy of Sciences, 2003)
Odor stimulation of olfactory sensory neurons (OSNs) leads to both the activation and subsequent desensitization of a heteromultimeric cyclic-nucleotide-gated (CNG) channel present in these cells. The native olfactory CNG channel consists of three distinct subunits: CNGA2, CNGA4, and CNGB1b. Mice in which the CNGA4 gene has been deleted display defective Ca(2+)/calmodulin-dependent inhibition of the CNG channel, resulting in a striking reduction in adaptation of the odor-induced electrophysiological response in the OSNs. These mutants therefore afford an excellent opportunity to assess the importance of Ca(2+)-mediated CNG channel desensitization for odor discrimination and adaptation in behaving animals. By using an operant conditioning paradigm, we show that CNGA4-null mice are profoundly impaired in the detection and discrimination of olfactory stimuli in the presence of an adapting background odor. The extent of this impairment depends on both the concentration and the molecular identity of the adapting stimulus. Thus, Ca(2+)-dependent desensitization of the odor response in the OSNs mediated by the CNGA4 subunit is essential for normal odor sensation and adaptation of freely behaving mice, preventing saturation of the olfactory signal transduction machinery and extending the range of odor detection and discrimination.